Peningkatan Kadar Ketoprofen Terdisolusi melalui Pembentukan Dispersi Padat menggunakan Polivinil Alkohol (PVA): The Increasing of Dissolved Ketoprofen Concentration through Solid Dispersion Formation using Polyvinyl Alcohol (PVA) - Sultan, Asriana; Ida, Nur; Ismail, Isriany (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Ketoprofen is included in the Class II of Biopharmaceutical Classification System (BCS) which has low solubility. Low solubility will affect the dissolution rate and the dissolved concentration, so the absorption and bioavailability are low as well. Several studies have been conducted to improve the solubility and the dissolution of drugs from these group, such as by solid dispersion system. This study aims to determine the effect of polyvinyl alcohol (PVA) on the dissolved concentration of ketoprofen in solid dispersion and in physical mixture, and to decidethe optimum formula.Solid dispersion and physical mixture of ketoprofen - PVA were formulated with the ratio of 1:1, 1:2 and 1:4, and then compared with the standard ketoprofen. Evaluation of solid dispersion was performed by the intervention test of PVA as a matrix on the maximum wavelength of standard ketoprofen using a UV-Vis spectrophotometer and the dissolution test in artificial gastric fluid media without pepsin using a basket stirrer at pH ± 1,2, the temperature of 37 ± 0.5ºC, and device speed of 50 rpm. The sample was collected at 10, 20, 30, 45, and 60 minutes. The amount of dissolved ketoprofen was determined by a UV-Vis spectrophotometer at a wavelength of 260 nm. The results showed that there was no shifting on maximum wavelength point in both solid dispersions and physical mixtures. The dissolved ketoprofen concentration that was represented in solid dispersion was greater than in physical mixture and standard ketoprofen. The highest dissolved ketoprofen concentration was indicated in solid dispersion formula with the ratio of 1:1.